Internet-memes as a phenomenon of information society - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article analyzes one of the modern phenomena of Internet communication – Internet meme. Attention is paid to the analysis of the communicative function of Internet memes.